Hyponatraemia caused by repeated cerebrospinal fluid drainage in post haemorrhagic hydrocephalus. Issue 5 (May 1983) - MacMahon, P; Cooke, R W
Abstract : Three hyponatraemic infants had post-haemorrhagic hydrocephalus which was treated by repeated drainage of cerebrospinal fluid. Each required oral sodium supplements. The concentration of sodium in the cerebrospinal fluid was such that as much as 3 mmol of sodium could have been removed with each ventricular tap. Serum sodium concentrations should be monitored closely in any infant requiring regular drainage of cerebrospinal fluid.